Home blood pressure monitoring: methodology, clinical relevance and practical application. Issue 9 (September 2021) - Parati, Gianfranco; Stergiou, George S.; Bilo, Grzegorz; Kollias, Anastasios; Pengo, Martino; Ochoa, Juan Eugenio; Agarwal, Rajiv; Asayama, Kei; Asmar, Roland; Burnier, Michel; De La Sierra, Alejandro; Giannattasio, Cristina; et al.
Abstract : N/A: The present paper provides an update of previous recommendations on Home Blood Pressure Monitoring from the European Society of Hypertension (ESH) Working Group on Blood Pressure Monitoring and Cardiovascular Variability sequentially published in years 2000, 2008 and 2010. This update has taken into account new evidence in this field, including a recent statement by the American Heart association, as well as technological developments, which have occurred over the past 20 years. The present document has been developed by the same ESH Working Group with inputs from an international team of experts, and has been endorsed by the ESH. Abstract : Supplemental Digital Content is available in the text